PENINGKATAN HASIL BELAJAR MEKANIKA REKAYASA DASAR MAHASISWA PROGRAM STUDI TEKNIK SIPIL MELALUI MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) - Rizky Febriani Pohan; Muhammad Rahman Rambe (CV. AFDIFAL MAJU BERKAH, 2022)
Basic Engineering Mechanics is a science that plays an important role in civil engineering disciplines, especially in the construction sector. In studying Basic Engineering Mechanics, a Project Based Learning model is needed that can help students to more easily apply it. This study aims to determine the increasing in learning outcomes of Basic Engineering Mechanics of Civil Engineering Study Program students through the application of Project Based Learning model. The type of research to be conducted is experimental research using the pretest-posttest control group design. The research subjects were students of the Civil Engineering Study Program, Graha Nusantara University, Padangsidimpuan for first semester in Academic Year 2021-2022, totaling 60 people. Research instrument in the form of pre-test and post-test. The data analysis technique used in this research is comparative descriptive analysis, while the increasing in student learning outcomes through the application of Project Based Learning (PjBL) model is calculated using g-factor (normalized gain score). Based on the research results obtained, it can be concluded that the Project Based Learning model can increase the learning outcomes of Basic Engineering Mechanics for Civil Engineering Study Program students by 37.74%. While the conventional learning model can only increase the learning outcomes of Basic Engineering Mechanics for Civil Engineering Study Program students by 31.41%. So that the Project Based Learning model is more effectively used in Basic Engineering Mechanics courses than conventional learning model.